The rock coast of South and Central America - Blanco-Chao, Ramon (2014)
The great variety of climatic conditions, tidal ranges and wave regimes of South and Central America act on a complex geology and tectonic framework. Many of the rock and cliffed coasts of South America are strongly controlled by the occurrence of extensive Cenozoic and Pleistocene sediments that crop out at the coast. Geology and the different uplift rates are a major factor inthe whole coastal geomorphology of South and Central America, and consequently are a very important control of the processes andlandforms of rock coasts. This chapter covers several aspects of the rock coast of South and Central America, with special attention to the combination of tectonic movements and Quaternary Pleistocene–Holocene sea-level changes